Global research trends on the relationship between IBD and CRC: a bibliometric analysis from 2000 to 2023 - Hao Zhang; Huiru Xin; Mengqi Zhao; Chenyang Bi; Yafei Xiao; Yifan Li; Changjiang Qin (BMC, 2024)
Abstract Objective This study aimed to conduct a bibliometric analysis of research articles on the relationship between inflammatory bowel disease (IBD) and colorectal cancer (CRC) using CiteSpace to summarize the current research status, hotspots, and trends in this field and present the results visually. Method Research articles on the relationship between IBD and CRC published from 2000 to 2023 and in English were selected from the Web of Science Core Collection (Woscc) database. The articles were downloaded as "full record and references". CiteSpace was used to conduct cooperative, cluster, co-citation, and burst analyses. Results The literature search revealed 4244 articles; of which, 5 duplicates were removed, resulting in the inclusion of 4239 articles in this study. The United States of America had the highest number of publications, with Mayo Clinic and Harvard University being the most active institutions, and Bas Oldenburg being the most active author. Collaboration among core authors was inadequate. JA Eaden was the most cited author, and CRC was the most common keyword. Burst analysis indicated that Sun Yat-sen University might be one of the institutions with a large contribution to this research field in the future. Cluster analysis showed that earlier research focused more on microsatellite instability, whereas "gut microbiota" and "oxidative stress" are considered current research hotspots and trends. Conclusion At present, the primary focus areas of research are "gut microbiota" and "oxidative stress". With the improvement of healthcare policies and standards, regular endoscopic monitoring of patients with IBD has become an indispensable diagnostic and therapeutic practice. More drugs will be developed to reduce the risk of progression from IBD to CRC. The findings of this study provide valuable insights into the relationship between IBD and CRC for researchers in the same field.